The behavior of Organic and Inorganic forms of Nutrients in the estuaries of Marqieh and Al-Housen rivers (shore waters of Tartous Governorate) - محمد , ميساء; حازم كراوي; فيروز درويش (Latakia University Journal -Basic Sciences Series, 2022)
In this research, the temporal and spatial changes in nutrient concentrations were studied throughout the year in each phase of their existence (dissolved inorganic, dissolved organic and particulate nutrient), Studying factors that affect the changes of its concentrations, estimating the primary productivity (concentrations of Chlorophyll a), and determining the limiting factor for growth in several locations in coastal waters of Tartous Governorate. Samples were collected from estuary areas of (Marqieh, Housen) at different salinity values. Semi-term water samples were collected during the period between (August 2020 and May 2021) In order to study the distribution of nutrients (nitrogen, phosphorous), Determination of Hydrochemical properties of water to identify its impact on nutrients distribution in studied areas. Highest concentrations of nutrients were observed at the estuary point of studied rivers, This point constituted the main source of nutrients in their various forms, These concentrations decreased with the distance from the estuary point during all marine sampling trips. Chlorophyll concentrations recorded two peaks (Spring and Autumn), which coincided with a decrease in concentrations of dissolved inorganic and dissolved organic nutrients, while concentration of particulate nutrients increased. Redfield ratio showed that phosphorous ions played the role of limiting factor for growth in all studied sites. The ∑N/P ratio was greater than Redfield ratio (N/P = 16) in 78% of samples in Marqieh estuary region and in 83% of samples in Housen estuary region. The DON/DOP ratio was greater than Redfield ratio in 94% of the samples in Marqieh estuary and in 89% of samples in Housen estuary region.